Depletion from Self‐Regulation: A Resource‐based Account of the Effect of Value Incongruence. Issue 2 (25th June 2015) - Deng, Hong; Wu, Chia‐Huei; Leung, Kwok; Guan, Yanjun
Abstract : Value incongruence between employees and organizations has been identified as a negative work condition. An attitude‐based account suggests that value incongruence gives rise to negative attitudes toward organizations and thus causes low performance. To complement this mechanism, we propose a resource‐based account based on ego‐depletion theory, which suggests that value incongruence consumes an individual's regulatory resources and leads to low work performance. In support of this view, results from 2 survey studies and a vignette experiment reveal that value incongruence is positively associated with ego depletion, which in turn is negatively related to work performance. The mediation effect of ego depletion is independent of the attitude‐based mechanism as represented by job satisfaction and affective commitment. Consistent with the affective consistency perspective, the relationship between value incongruence and ego depletion is stronger among employees high in positive affectivity and weaker among employees high in negative affectivity. The corresponding moderated mediation analysis shows that the indirect effects of value incongruence on work performance through ego depletion vary as a function of positive and negative affectivity. This investigation unravels the self‐regulatory consequence of value incongruence and shows that the resource‐based mechanism of value incongruence operates differentially as a function of dispositional affectivity.